HUBUNGAN PERAN IBU DALAM MEMBERIKAN INFORMASI DENGAN PENGETAHUAN TENTANG MENARCHE PADA REMAJA PUTRI USIA 10-13 TAHUN DI SEKOLAH DASAR MENANGGALKECAMATAN MOJOSARIMOJOKERTO - Purwati, Heni; Dewi Ardiyanti, Novi (JURNAL KEPERAWATAN BINA SEHAT, 2016)
Menarche is usually experienced by women. And make something that makes young women feel troubled when the mother does not play a role in providing information. The purpose of this research is to know the relationship between the mothers role in providing information and knowledge about the adolescent age of menarche in teens 10-13 years at SDN Menanggal sub-district of Mojokerto Regency Mojosari as many as 55 young women ages 10-13 year old to get a sample of 55 young women taken with Total sampling. Its independent variable role of the mother in its dependent variables provide information and knowledge about adolescent menarche. The Data collected by using questionnaire. The results showed that most respondents did not carry out the mothers role in providing information to young women of 38 (69,1%) respondents. Nearly half of respondents knowledgeable less of 23 (41.8%) respondents. After the accumulated data processing is carried out and continued with the Chi Square test with the help of SPSS 20.0. The results showed ρ < α (0,001 < 0.05), so that H0 is rejected and accepted which means no H1 is the relationship between the mothers role in providing information and knowledge about adolescent menarche at young women aged 10-13 years at SDN Menanggal sub-district of Mojokerto Regency Mojosari This is because the majority of mothers considered taboo to discuss matters such as menarche to teenage daughter. Lack of knowledge about the menarche this will affect ones actions, because someone will behave like what they know and are considered to be the most correct.Key words: maternal Role, knowledge of adolescents, menarche.